SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE FUZZY SUGENO UNTUK MENENTUKAN CALON PRESIDEN MAHASISWA DI UNIVERSITAS ASAHAN - Muhammad Yasin Simargolang; Helki Saidah Tamba ((JurTI) Jurnal Teknologi Informasi, 2018)
Abstract - The student president is a student leader who aims to mediate students with the rector. Every year a student presidential election will be held. To carry out the elections, of course, they must have candidates as candidates. To become a candidate, the committee selects candidates based on the conditions that have been determined. The selection is done manually. However, candidates come from different faculties and departments which result in all its limitations, the committee will have difficulties and it will take a relatively long time to determine the candidates. Therefore, building a decision support system using the Sugeno fuzzy method to determine student presidential candidates is a good idea. This study aims to design and implement a decision support system with fuzzy Sugeno method, to facilitate the committee in working. This study uses a library research method. Where the source of information is obtained from books, journals, and others. To design a system created using UML. Based on system design, implementation and testing, the conclusion is that a decision support system with fuzzy sugeno method can determine student presidential candidates. The system built can be used as an alternative in selecting student presidential candidates because it can facilitate the committee in processing data to make decisions. Keywords - Prospective Student President, Decision Support System, Fuzzy Sugeno